About the Geological Structure of the Agstafachay-Ganjachay Valley Plain - Ibrahimova, S.I.; Aghamaliyeva, G.K.; Nasibov, A.Z. (Herald of Azerbaijan Engineering Academy, 2024)
Jurassic, Cretaceous, Paleogene, Neogene and Quaternary sediments are involved in the geological structure of the Agstafachay-Ganjachay valley plain. Mesozoic sediments form the mountain outcrops of the Lesser Caucasus and reach the earth's surface along the mountain front. In the remaining areas, it is quite deep. Paleogene and Neogene sediments come to the surface in the southeast of the massif. All these sediments are covered by younger sediments in the foothill plain area.